2014
DOI: 10.1136/bmjqs-2013-002315
|View full text |Cite
|
Sign up to set email alerts
|

Improved patient safety through reduced airway infection rates in a paediatric cystic fibrosis programme after a quality improvement effort to enhance infection prevention and control measures

Abstract: ObjectiveTo reduce the risk of pathogen transmission between patients with cystic fibrosis (CF) and decrease the rate of acquisition of new CF pathogens in our patients.DesignUsing the Model for Improvement, we developed a new process for infection prevention and control in our outpatient CF clinics.SettingPaediatric CF programme at Ann & Robert H. Lurie Children's Hospital of Chicago; approximately 180 paediatric patients aged birth to 21 years.ParticipantsAll paediatric patients enrolled in the Cystic Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
(47 reference statements)
0
16
0
Order By: Relevance
“…30 Support for acquisition of MRSA in health-care settings is provided by a report that found that more stringent infection prevention and control strategies, which included universal contact precautions, significantly reduced MRSA in a pediatric CF clinic. 31 Studies to find effective therapeutic approaches to eradication are ongoing. 32,33 We found that the prevalence of S maltophilia increased.…”
Section: Discussionmentioning
confidence: 99%
“…30 Support for acquisition of MRSA in health-care settings is provided by a report that found that more stringent infection prevention and control strategies, which included universal contact precautions, significantly reduced MRSA in a pediatric CF clinic. 31 Studies to find effective therapeutic approaches to eradication are ongoing. 32,33 We found that the prevalence of S maltophilia increased.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the lack of knowledge of the recommendations, they identified other barriers, such as disagreement with the recommendations, organizational constraints to following the recommendations, and ambiguity in the guidelines. Although there is more than one barrier to the implementation of infection-control guidelines in any healthcare setting, 7 lack of awareness is a significant one. Change begins with awareness.…”
Section: Awareness Of Guidelinesmentioning
confidence: 99%
“…Infection with MRSA remains an important problem in cystic fibrosis where primary prevention through infection control is the best strategy . Phenotypic methicillin resistance is classically encoded by the mec A gene, but non‐genetic resistance mechanisms are also found.…”
Section: Resultsmentioning
confidence: 99%
“…Such factors are multi‐factorial and include climate, that is, higher rates in warmer climate, social and healthcare factors. For example, extensive versus more restrictive use of antibiotics and hospital infection control policies in CF and non‐CF . Specifically, antimicrobial stewardship programs with reduced use of antibiotics are associated with reduced rates of MRSA …”
Section: Epidemiologymentioning
confidence: 99%